INTERNALISASI NILAI-NILAI IBADAH SYAUM DI PONDOK PESANTREN : Studi Kasus Kesalehan Sosial di Pondok Pesantren Al-Muhajirin Purwakarta - Burhanudin, - (2010)
The background of the study is the phenomonon in which moslems have an erroneous tendency in valuing the action of fasting by only doing the ritual obligation. #0;alat, zakat, hajj and umrah are being conducted well but his/her daily action has not reflected a unity of a moslem's personality. Dahlan (2003: 8) described that in our daily life, there is a phenomenon of someone who shows an extensive ritual piety (doing #1;alat la diligently, doing ritual obligatory fasting and sunah fasting, taking hajj and umrah several times), but letting poverty happens. In fact it is clearly as if she is numb for the poverty around him or her. The objective of this study is to find out a learning strategy of self- and social-piety values in Pondok Pesantren Al-Muhajirin Purwakarta. The approach used in this study is qualitative approach with multi methods. The result showed that there are still santri (Pondok Pesantren students) who act unproperly to the religious values, in the other side, Pondok Pesantren itself has not developed a learning strategy to improve piety values learning. In this study, there are nine actions which are found to be the realization of social-piety value i.e. care, empathy, patient, responsible, grateful, generous, honest, forgiveness, and helpful. This nine actions can be a reference in the learning process of social piety. Furthermore, this study gains a learning strategy of social-piety in the Pondok Pesantren. The strategy is an operational steps in the learning process of social-piety, which are: a) preparation; the learners are prepared to a conducive learning situation, b) muqaddimah (introduction); the explanation of the importance of social-piety in daily life, c) checking the learning environment so the learning situation remains conducive, d) strengthening and giving enrichment so the given material can be well internalized as an unseparated part of the students, e) evaluation; cognition aspect is carried out by giving oral and or written formative which consist of social-piety values, and internalization aspect and attitude by conducting learners observation when they are communicating and interacting with their peers, teachers, parents, and or the guests who were visiting the pondok pesantren. The indication of piety can be observed through respecting attitude such as being polite and tawaďďu in their action and utterances, and e) closing and conclusion by strengthening and giving enrichment to the materials related with social-piety values. Concluding the learning process can also be done by doing question and answer session between students and teacher. The result of this study is recommended to be continued in formal education, especially about the learning models of social-piety values as one of students' personality development aspect, and institution development to improve self- and social-piety values as one of the national education goals which is to develop a united human; a kaffah human being.